2021
DOI: 10.1002/cpt.2351
|View full text |Cite
|
Sign up to set email alerts
|

Emulating Control Arms for Cancer Clinical Trials Using External Cohorts Created From Electronic Health Record‐Derived Real‐World Data

Abstract: Electronic health record (EHR)-derived real-world data (RWD) can be sourced to create external comparator cohorts to oncology clinical trials. This exploratory study assessed whether EHR-derived patient cohorts could emulate select clinical trial control arms across multiple tumor types. The impact of analytic decisions on emulation results was also evaluated. By digitizing Kaplan-Meier curves, we reconstructed published control arm results from 15 trials that supported drug approvals from January 1, 2016, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 45 publications
(142 reference statements)
4
27
0
Order By: Relevance
“…For endpoints other than OS, especially those that typically depend on radiographic criteria such as for PFS and ORR, the utility of using RWD to serve as external controls is currently unclear. Our current study builds upon the current literature by: (i) extending the work of Carrigan and colleagues for the OS endpoint to include more recent IMpower trials; (ii) replicating trial control arms with rwPFS and rwRR endpoints for the first time in these IMpower trials; and (iii) improving upon the methodology used in recent publications by incorporating patient-level data for clinical trials (7,19).…”
Section: Discussionmentioning
confidence: 98%
“…For endpoints other than OS, especially those that typically depend on radiographic criteria such as for PFS and ORR, the utility of using RWD to serve as external controls is currently unclear. Our current study builds upon the current literature by: (i) extending the work of Carrigan and colleagues for the OS endpoint to include more recent IMpower trials; (ii) replicating trial control arms with rwPFS and rwRR endpoints for the first time in these IMpower trials; and (iii) improving upon the methodology used in recent publications by incorporating patient-level data for clinical trials (7,19).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Tan et al (2021) studied 15 trials across multiple tumor types and found that the majority of trials had HR RWD ranging from 0.66 to 1.09 for the OS endpoint [ 23 ]. Such evaluations provide a sense of how much residual bias may be plausible and relevant when selecting the value of tuning parameters and assessing the overall suitability of a hybrid design for a future cancer trials with similar I/E criteria.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…From an analytical perspective, of the four main steps in a hybrid controlled trial beyond typical RCT procedures (external cohort selection; baseline covariate balance; endpoint, index dates, and follow-up time definition; implementation of a borrowing method), the first three are common to fully external controls, and have been described before [ 17 , 19 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations